2001
DOI: 10.1002/1097-0215(20010920)95:5<307::aid-ijc0153>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Reverse transcription-polymerase chain reaction assay for multiple mRNA markers in the detection of breast cancer metastases in sentinel lymph nodes

Abstract: The identification of specific tumor mRNA markers by reverse transcription‐polymerase chain reaction might be a valuable diagnostic adjunct for the detection of breast cancer metastases in axillary sentinel lymph nodes (SLNs). In this study we have compared the diagnostic accuracy of an extensive histopathologic examination of 146 SLNs from 123 breast carcinoma patients with that of the evaluation of 5 mRNA markers. When analyzed individually, none of the different markers attained a sensitivity higher than 77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
45
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 34 publications
(94 reference statements)
1
45
0
Order By: Relevance
“…Therefore, a tumour-free sentinel lymph node implies the absence of lymph node metastases in the entire lymphatic basin. This sentinel node concept had been previously confirmed by H&E examinations, immunohistochemical study and nonquantitative RT -PCR assays (Giuliano et al, 1994;Albertini et al, 1996;Veronesi et al, 1997;Krag et al, 1998;Kataoka et al, 2000;Manzotti et al, 2001;Branagan et al, 2002;Ishida et al, 2002).…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…Therefore, a tumour-free sentinel lymph node implies the absence of lymph node metastases in the entire lymphatic basin. This sentinel node concept had been previously confirmed by H&E examinations, immunohistochemical study and nonquantitative RT -PCR assays (Giuliano et al, 1994;Albertini et al, 1996;Veronesi et al, 1997;Krag et al, 1998;Kataoka et al, 2000;Manzotti et al, 2001;Branagan et al, 2002;Ishida et al, 2002).…”
mentioning
confidence: 61%
“…Recently, RT -PCR assays with tumour-specific gene markers such as CK19, CEA, MUC1, PIP, Mapsin and mammaglobin B have been widely used to detect occult metastasis in cancer patients (Noguchi et al, 1994(Noguchi et al, , 1996Schoenheld et al, 1994;Mori et al, 1995Mori et al, , 1998Kataoka et al, 2000;Masuda et al, 2000;Manzotti et al, 2001;Mitas et al, 2001). To date, however, no marker that is expressed in all breast cancer tissues, but not in normal lymph node has been available, partly because of the heterogeneity of marker gene expression in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The two specific markers identified, mammaglobin and CK19, have been previously published as potentially useful components of multimarker panels for the identification of occult metastasis in breast lymph nodes. 12,32,33 However, previous studies have also concluded that both markers are expressed in the lymph nodes of 20 to 40% of patients categorized as lymph node negative by standard histological analysis. 10,11 It has also been reported that lymph nodes from a high percentage of cancer-free patients express CK19.…”
Section: Discussionmentioning
confidence: 99%